2015
DOI: 10.1017/s1751731114002365
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of pork longissimus muscle pH to mitochondrial respiratory activities, meat quality and muscle structure

Abstract: The way the pH falls post-slaughter has an impact on meat quality. Pork longissimus muscles (n = 48) were sorted in fast-(FG) (n = 15) and normal glycolysing (NG) (n = 33) muscles according to the post-slaughter pH 45 min values (FG < 6.0; NG > 6.0). FG muscles (5.84 ± 0.04) compared with NG muscles (6.27 ± 0.04) were accompanied with higher temperature, electrical conductivity, lightness and yellowness, and reduced grill loss and shear force values ( P < 0.05), but there were no pH-dependent changes of the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…The enzymes in the cytoplasm generally play an essential role in a neutral environment. Lower pH caused the active core group of the enzyme to deviate from its optimal dissociation state, reducing its capacity to bind to the substrate and catalytic activity 25,35 . In the present study, the fast pH decline group had greater ROS levels than the slow group, which could be owing to changes in the structure and activity of ROS scavenging enzymes by rapidly declining muscle pH.…”
Section: Resultsmentioning
confidence: 99%
“…The enzymes in the cytoplasm generally play an essential role in a neutral environment. Lower pH caused the active core group of the enzyme to deviate from its optimal dissociation state, reducing its capacity to bind to the substrate and catalytic activity 25,35 . In the present study, the fast pH decline group had greater ROS levels than the slow group, which could be owing to changes in the structure and activity of ROS scavenging enzymes by rapidly declining muscle pH.…”
Section: Resultsmentioning
confidence: 99%
“…Phung et al (2013) showed that bovine semimembranosus temperature was negatively associated with OCR. Others have observed that porcine LL with rapid pH decline exhibits a more profound decrease in mt respiratory activity in comparison to LL with slower pH decline (Werner et al, 2010;Popp et al, 2015). Paradoxically, rapid pH decline in Dia does not appear to negatively impact mt function.…”
Section: Muscle Ph and Temperature Declinementioning
confidence: 94%
“…Mitochondria are also known to play a role in postmortem pH decline (Popp et al, 2015;Matarneh et al, 2016). Mitochondria influence pH decline because functioning mitochondria will allow pyruvate to be metabolized by the citric acid cycle instead of being converted to lactate.…”
Section: Supplemental Tablementioning
confidence: 99%